Welded steel I-section columns: Residual stresses, testing, simulation and design. (1st May 2023) - Yun, Xiang; Zhu, Yufei; Meng, Xin; Gardner, Leroy
Highlights: A new residual stress model for S235 to S960 steel welded I-sections has been proposed. Tests on HSS homogeneous and hybrid welded I-section columns buckling about the major axis have been carried out. Numerical models have been established and validated against test results. Numerical parametric studies have been performed considering different key parameters. Current codified design rules on flexural buckling of welded I-section columns have been assessed. A new design method has been devised providing more accurate and consistent flexural buckling resistances. Abstract: The flexural buckling behaviour and design of homogeneous and hybrid welded I-section columns, considering a wide range of steel grades, are investigated in the present study. Residual stresses are first examined through the statistical analysis of 71 existing experimental results collected from the literature; on the basis of the findings, a new residual stress model for S235 to S960 steel welded I-sections is proposed. Experiments on a total of five pin-ended homogeneous (S690) and hybrid (S355 web and S690 flanges) welded I-section columns buckling about the major axis are then presented. In parallel with the experimental programme, finite element (FE) models were created and validated against the experimental results obtained from the present study, as well as those collected from the literature. The developed FE models were shown to be capable of accurately replicating the key experimental responses, and were then utilised to carry out extensive parametric studies, through which additional 6000 numerical column buckling data covering a wide range of steel grades, cross-section geometries and member slendernesses were generated. The combined experimental and numerical data were used to evaluate the accuracy of the flexural buckling design rules for welded I-section columns set out in the current European and North American design standards, where shortcomings relating to the consideration of steel grade were identified. A modified Eurocode 3 (EC3) method was devised to reflect the influence of yield strength on the buckling resistances of welded I-section columns more systematically and shown to provide substantially improved resistance predictions in terms of accuracy and consistency; the reliability of the modified approach was statistically verified following the procedure set out in Annex D of EN 1990 and is considered to be suitable for incorporation into future revisions of Eurocode 3.